Nurses' Risk Perception of Adverse Events and Its Influencing Factors: A Cross-Sectional Study - Longti Li PhD; Chunqi Ai MD; Menghe Wang MS; Xiong Chen PhD (SAGE Publishing, 2024)
To investigate clinical nurses' perception of adverse event risk and to analyze its influencing factors. A proportional stratified random sampling method was applied to recruit nurses from a hospital in Shiyan City, Hubei Province, China. The Nursing Adverse Event Risk Perception Scale, Organizational Support Questionnaire, Nurse Manager Leadership Behavior Questionnaire, Nursing Safety Behavior Questionnaire, and Burnout scale was used to investigate 1084 nurses. Univariate analysis, Pearson correlation analysis, and multiple linear regression analysis were used to analyze the influencing factors. The scores of the Nurses' Risk Perception of Adverse Nursing Event Scale, Organizational Support Questionnaire, Nurse Manager Leadership Behavior Questionnaire, Nursing Safety Behavior Questionnaire, and Burnout Scale were 14.98 ± 5.39, 52.57 ± 10.00, 88.98 ± 21.08, 56.42 ± 5.03, 30.90 ± 21.49, respectively. According to the correlation analysis, nurses' perception of adverse nursing events was positively correlated with the sense of organizational support (r = .457, P  < .01), head nurses' leadership behavior (r = .348, P  < .01), and nurse safety behavior (r = .457, P  < .01), and negatively correlated with the level of burnout (r = −.384, P  < .01). According to the Regression analysis, nurses' departments (β = .226, P  < .001), daily working hours (β = 1.122, P  < .001), adverse events experience (β = −1.505, P  < .001), organizational support (β = .105, P  < .001), head nurses' leadership behavior (β = .072, P  < .001), and burnout (β = −.052, P  < .001) held an influence on nurses' risk perception of adverse nursing event. These factors explained 42.5% of the total variation. Nurses' risk perception of adverse nursing events needs to be improved. Nursing managers need to strengthen organizational support for nurses, change the leadership behavior of nurse managers, reduce nurses' burnout, improve nurses' risk perception of adverse nursing events, prevent adverse events, and ensure patient safety.